2014
DOI: 10.1002/jbm.b.33139
|View full text |Cite
|
Sign up to set email alerts
|

Histometric analysis and topographic characterization of cp Ti implants with surfaces modified by laser with and without silica deposition

Abstract: Biologic behavior of the bone tissue around implants with four different surfaces was evaluated. The surfaces were: modified by laser (LS); modified by laser with sodium silicate deposition (SS); and commercially available surfaces modified by acid etching (AS) and machined surface (MS). Topographic characterization of the surfaces was performed by scanning electron microscopy (SEM)- energy dispersive X-ray spectrometry (EDX) before experimental surgery. Thirty rabbits received 60 implants in their right and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Specifically, the BA values were calculated by dividing the area of bone tissue present by the total tissue volume present in the ROI (Souza et al. ). One single and experienced observer has performed the descriptive histologic and histomorphometric evaluation.…”
Section: Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…Specifically, the BA values were calculated by dividing the area of bone tissue present by the total tissue volume present in the ROI (Souza et al. ). One single and experienced observer has performed the descriptive histologic and histomorphometric evaluation.…”
Section: Methodsmentioning
confidence: 73%
“…The region of interest (ROI) and BIC and BA calculations were conducted among the three most coronally situated threads that were located in the cancellous bone on each size of the implant. Specifically, the BA values were calculated by dividing the area of bone tissue present by the total tissue volume present in the ROI (Souza et al 2014). One single and experienced observer has performed the descriptive histologic and histomorphometric evaluation.…”
Section: Histomorphometric Analysismentioning
confidence: 99%
“…Both in vitro [38,39] and in vivo studies [40,41] reported a positive correlation between fibrin adhesion and surface wettability. Fibrin adhesion is influenced by different parameters: Blood drop extension, gravity of the drop, liquid characteristics, and thermodynamics aspects [42].…”
Section: Discussionmentioning
confidence: 98%
“…Topographic properties and physicochemical surface of the implants are essential in the early stages of osseointegration, as they are responsible for the biological responses of biomaterials [6][7][8][9][10][11][12]. Accelerated bone formation and bone resistance can provide better implant stability during the bone healing process allowing faster implant placement and prosthetic rehabilitation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Another surface modification employed to accelerate implant osseointegration and favoring bone tissue interaction is surface coated with ceramic Ca-P [12,[27][28][29][30]. The Ca-P is released in the peri-implant region increasing the saturation of body fluid with consequent biological apatite precipitation on the implant surface.…”
Section: Introductionmentioning
confidence: 99%